Implementation of Learning Theory According to Behavioristic Psychology in Vocational Education - Helpi Nelwatri; Neviyarni Neviyarni (Postgraduate School, Universitas Negeri Padang, 2022)
The flow of behavioral psychology learning theory is one of the learning theories that prioritize changes in student behavior as a result of stimuli and responses. Learning is a form of change experienced by students, through the interaction between stimulus and response that aims to modify student behavior. Watson explained that student behavior is the result of innate influences from family and environment. While Pavlov explained that it refers to several training processes in vocational education, namely the training process between one stimulus and another to be able to develop a response. Meanwhile, Skinner argues that the relationship between stimulus and response occurs because through interaction with the environment the next change is caused by changes in behavior. Thus, it can be concluded that behavioral psychology theory focuses more on developing student behavior in a better direction, especially in vocational education. In principle, behavioral psychology learning theory is very relevant if it is implemented in the design of learning methods in vocational education.